Morphological abnormalities in mitochondria of the skin of patients with sporadic amyotrophic lateral sclerosis - Gabriel E. Rodríguez; Deniselle M. Claudia González; Gisella M. Gargiulo Monachelli; Juan J. López Costa; Alejandro F. de Nicola; Roberto E. P. Sica (Arquivos de Neuro-Psiquiatria)
OBJECTIVES: Mitochondrial dysfunction has been reported in the central nervous system, hepatocytes and peripheral blood lymphocytes from patients with sporadic amyotrophic lateral sclerosis (SALS). However, the status of skin mitochondria has not been reported, in spite of the fact that SALS patients present skin abnormalities. The objective of the present study was to compare mitochondrial ultrastructural parameters in keratinocytes from patients with SALS and healthy controls. METHODS: Our study was based on the analysis of 112 skin mitochondria from 5 SALS patients and 99 organelles from 4 control subjects by electron microscopy. RESULTS: Computerized image analysis showed that mitochondrial major axis length, area and perimeter of the organelle were significantly smaller in SALS respect of healthy control subjects. Morphologically, SALS mitochondria presented cristolysis and breakage of the outer membrane. CONCLUSIONS: Mitochondrial dysfunction in the skin may possibly reflect changes occurring in mitochondria of the central nervous system. The analysis of mitochondrial morphology in this tissue may be of value to follow disease progression and, eventually, the effectiveness of current therapies for SALS.